Sistem Rekrutmen Sumber Daya Manusia (Guru) di MTsS Insan Qur’ani - Muhammad Yasir (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This research aims to document and explain the human resources (HR) recruitment system at the Insan Qur'ani Private Madrasah Tsanawiyah (MTsS). MTsS Insan Qur'ani is an educational institution that is committed to developing students' potential holistically, including academic and moral aspects. In this context, the teacher recruitment system has an important role in shaping the quality of education provided by the institution. This research uses a descriptive approach to describe the steps and basic principles that form the basis of the teacher recruitment system at MTsS Insan Qur'ani. Data was collected through interviews with related parties, document review, and direct observation of the recruitment process carried out by the institution. Data analysis was carried out to identify the policies, strategies and procedures involved in managing human resources in these educational institutions. The research results show that MTsS Insan Qur'ani implements a holistic approach in teacher recruitment, considering not only aspects of academic expertise but also Islamic values, professional ethics and interpersonal skills. This recruitment process is directed at ensuring that each selected teacher is committed to supporting the institution's vision and mission.